Laporan Pelatihan Penyusunan Program Latihan Olahraga Bagi Guru PJOK Di Kecamatan Majenang Tahun 2023 - Raditya Pratama; Syahida Cahya Allistia; Dewo Panca Lesmana (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2023)
The activity aimed to improve penjasorkes teacher ability in programming sport training. Participants of this program were sport teachers in Elementary Schools, Junior High Schools, Senior High School, and Vocational High Schools in Majenang District who were in a total of 30 people. This workshop was held in two steps, the first step was a conference about the training periodization concept and its supporting theories, and the second step was programming sports training for athletes at the student level. This workshop showed that generally this activity was held by the planning. All teachers understood the periodization concept and were able to program the training. Therefore, this activity positively contributed to the sports teacher as one of the potentials to develop sports activity in Majenang District.